(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Near-field communication (NFC) is a short-distance wireless data transmission technology with potential for wearable sensors. Xu et al. (2020) developed a battery-free smart textile patch with an NFC antenna and a temperature sensor (STP-NFC) [1]. To address potential issues with the testing protocol that could affect the accuracy and precision of temperature measurement from the STP-NFC, a validation experiment was conducted at a fixed room temperature of 20^◦C. This was done using a commercial IR imager to compare the results with the STP-NFC results. Results showed excellent accuracy with an average temperature of 21.50^◦C and a difference of only 0.36^◦C from an IR imager’s reading. The STP-NFC also had excellent precision with a small standard deviation of 0.83. Optimal performance was achieved with a 6 mm distance, a 150-second time interval, and a 4-second scanning duration for each scan. Additionally, the gage repeatability and reproducibility (R&R) study has been conducted to assess the STP-NFC measurement system’s consistency, and the STP-NFC’s reproducibility has been demonstrated. These results have implications for developing reliable wearable medical monitoring devices using NFC technology.